Access of the patient to the cancer network under the Sixty-Day Law: Integrative Review - Lombardo, Mariela Santos [UNESP]; Popim, Regina Celia [UNESP] (Assoc Brasileira Enfermagem, 2020)
Objectives: to analyze Brazilian scientific production on patient access to the oncology network under the Sixty-Day Law. Methods: integrative review of the literature in the databases Lilacs, PubMed and Scielo. The descriptors used were: neoplasms, health services accessibility, early detection of cancer. Articles published from 2015 to March 2019 were included. Results: 17 articles were analyzed and four themes emerged: inequality in access; qualification of Primary Care professionals; time as a determinant factor; information system as limiting factor. Conclusions: the access to the oncology network is unequal and there are several barriers faced by the users. A continuing education of health professionals is necessary to implement preventive strategies. Treatment initiation is late, showing noncompliance with the law. The health care network is highly fragmented, there is lack of coordination between the services and, consequently, there is a lack of patient follow-up.
Keywords: Neoplasms; Health Services Accessibility; Early Detection of Cancer; Review; Cancer Institute